2011
DOI: 10.1007/s10723-011-9179-y
|View full text |Cite
|
Sign up to set email alerts
|

Job Allocation Strategies with User Run Time Estimates for Online Scheduling in Hierarchical Grids

Abstract: We address non-preemptive nonclairvoyant online scheduling of parallel jobs on a Grid. We consider a Grid scheduling model with two stages. At the first stage, jobs are allocated to a suitable Grid site, while at the second stage, local scheduling is independently applied to each site. We analyze allocation strategies depending on the type and amount of information they require. We conduct a comprehensive performance evaluation study using simulation and demonstrate that our strategies perform well with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Ramirez-Alcaraz et al [19] have analyzed different Grid allocation strategies depending on the type and amount of information they require, and they found that information about users' runtime estimate and local schedules does not help to significantly improve the outcome of the allocation strategies. They concluded that quite simple schedulers with minimal information requirements can provide good performance.…”
Section: Related Workmentioning
confidence: 99%
“…Ramirez-Alcaraz et al [19] have analyzed different Grid allocation strategies depending on the type and amount of information they require, and they found that information about users' runtime estimate and local schedules does not help to significantly improve the outcome of the allocation strategies. They concluded that quite simple schedulers with minimal information requirements can provide good performance.…”
Section: Related Workmentioning
confidence: 99%
“…In this approach [11], [14 ], [15] number of Hosts required two, waiting time reduces , L 3 Backfill with L 2 so consumer fills happy as compare to previous approach and waiting time of lease L 3 reduces, number of hosts required two and conserve more energy as shown in fig.2. …”
Section: Eesas With Easy Backfilling Fcfsmentioning
confidence: 99%
“…VM 11 VM 12 EESAS is implement on base of three conditions i) No workload i.e zero workload ii) Minimum workload and, iii) Maximum workload , when minimum workload then start virtual machine as per VM request, if no workload then do not start any VM for conserving energy purpose, maximum workload then apply migration of VM , clone one VM to multiple VM , in this EESAS with easy backfilling FCFS only allocation of job to VM is change.…”
Section: Pseudo Code Of Eesasmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramírez-Alcaraz et al [44] evaluate scheduling heuristics and optimize a combined objective for parallel jobs, because they assess that computing a Pareto frontier in a GRID environment is too slow. However, approximating the Pareto frontier for the cases we demonstrated here using ExPERT takes only minutes, which we do not consider "too slow" for a BoT that runs for hours.…”
Section: Related Workmentioning
confidence: 99%